(untitled) (Revista de Investigaciones Universidad del Quindío, 2009)
A preliminary phytochemical study was conducted with leaves of Lippia origanoides H.B.K., carried out by several extraction methods (percolation, Soxhlet and leaching), using solvents of different polarities such as petroleum ether, hexane, dichloromethane, and ethanol. The content of secondary metabolites was analyzed found in polar extracts flavonoides, tannins, cardiac glycosides, hydroquinone and alkaloids, and in the nonpolar extracts, carotenoids, cardiac glycosides and sterols. The antimicrobial activity of polar and nonpolar extracts was evaluated by the disk diffusion method (Kirby-Bauer) modified, using Gram-negative and Gram-positive bacteria, fungi and yeast, noting that the nonpolar extracts showed activity of grown inhibition of the microorganism test, whereas the polar extracts did not show activity to the same microorganisms.